Большая книга сказок - Чуковский Корней Иванович (РОСМЭН, 2019)
Экземпляры: ф.6 (20210315) / Инвентарный номер: 3645 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5